2015
DOI: 10.1111/and.12440
|View full text |Cite
|
Sign up to set email alerts
|

Elastography to assess the effect of varicoceles on testes: a prospective controlled study

Abstract: Varicoceles are the most common and treatable cause of male infertility. The pathophysiology of varicoceles primarily includes elevated temperature, adrenal hormone reflux, gonadotoxic metabolite reflux, altered testicular blood flow, antisperm antibody formation and oxidative stress. The diagnosis of a varicocele is mainly clinical. However, a Doppler ultrasound is used to obtain clinical data and to more accurately measure testicular size. Acoustic radiation force impulse (ARFI) is an additional technique to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
58
4
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 22 publications
6
58
4
2
Order By: Relevance
“…[4,23,24] Tissue elasticity generally correlates with pathological conditions of the testicular parenchyma In most of the cases, a normal testicular biopsy excludes the diagnosis of testicular pathologies. [25] Some focal testicular lesions such as testicular microlithiasis, azoospermia and lesions with a diameter of <10 mm, particularly if they are not palpable, were investigated with the use of sonoelastography technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,23,24] Tissue elasticity generally correlates with pathological conditions of the testicular parenchyma In most of the cases, a normal testicular biopsy excludes the diagnosis of testicular pathologies. [25] Some focal testicular lesions such as testicular microlithiasis, azoospermia and lesions with a diameter of <10 mm, particularly if they are not palpable, were investigated with the use of sonoelastography technique.…”
Section: Discussionmentioning
confidence: 99%
“…Dede et al [24] investigated the relationship between elastography scores, serum FSH levels and varicocele. They concluded that testicular elasticity was inversely correlated with serum FSH and varicocele grade.…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic radiation force impulse (ARFI) elastography represents one of the main types of elastography currently in use, involving the estimation of shear wave speed. In a prospective controlled study of 30 men with clinical varicocele and 30 controls, Dede et al[61] concluded that ARFI elastography may be used to assess the early damage of testicular structure by varicocele[61]. Mean elastography results were significantly different between the two groups and significantly lower in testes with varicoceles.…”
Section: Us In the Evaluation Of Intratesticular Microcirculation In mentioning
confidence: 99%
“…Significant negative correlations between FSH and testis elasticity was also reported. Additionally, a negative correlation was determined between varicocele grade and elasticity of testes[61]. …”
Section: Us In the Evaluation Of Intratesticular Microcirculation In mentioning
confidence: 99%
“…that testicular elasticity was negatively associated with varicocele grade by ultrasound elastography(Dede et al, 2016). Recently, magnetic resonance imaging (MRI) as a noninvasive imaging technique has been performed to detect early signs of testes dysfunction in men with varicocele.…”
mentioning
confidence: 99%